Building Trust and Leadership: The Impact of Management Control Systems and Human Resource Competence on Financial Performance. Study at Perumda BPR Garut - Tita Rachtawati Santanu (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This research aims to explore the influence of human resource (HR) competency, management control systems, leadership, and trust on financial performance at Perumda BPR Garut. Data analysis and hypothesis testing were carried out to understand the relationship between these variables. The research results show that HR competency does not have a significant influence on financial performance, but has a positive and significant relationship with leadership and trust. The management control system shows a positive and significant influence on financial performance, leadership and trust. Leadership does not show a significant relationship with financial performance, while trust shows a positive and significant relationship with financial performance. In the mediating role, leadership does not mediate the influence of HR competency on financial performance, while trust mediates the influence of the management control system on financial performance. This research emphasizes the importance of effective management control systems and building trust in organizations to improve financial performance. These findings provide guidance for managers and organizational leaders in designing holistic strategies to achieve financial and operational success.